The 2024 Climate Tragedy in Rio Grande do Sul, Brazil. Notes on a foreseen catastrophe - Ruckert, Aldomar Arnaldo; Vicente, Francisco Jorge; Gomes, Luis Fabiano Ribeiro (Geografares, 2024)
This brief account captures the experiences and observations recorded on-site by the authors during and after the climate disaster that struck the state of Rio Grande do Sul from late April through May 2024. This report aims to consolidate information on what is regarded as one of the most severe climate disasters in Brazil from the onset of the catastrophe to the end of October 2024. For this purpose, we gathered data from various official and unofficial sources, fellow researchers from several universities, online news outlets, social media, and personal testimonies collected during and after the catastrophic events.